Encouraging Socialization: Essential in Leading to Up-gradation of Personality Traits - Dr. Radhika Kapur, (Indian Journal of Management and Language (IJML), 2025)
The individuals, belonging to all age groups, occupations, communities and socio-economic backgrounds are required to acknowledge the meaning and significance of socialization. From the stage of early childhood, the individuals need to realize that beyond their homes also there is a world, with which they are required to communicate with. Hence, within personal and professional lives of the individuals, they need to encourage socialization. This needs to be reinforced with family and community members. In order to carry out this task, one needs to be well-informed in terms of communication ethics, i.e. making use of polite language and decent words; treating others with respect and courtesy; making provision of factual information; reinforcing the traits of efficiency, honesty and truthfulness; depicting the traits of helpfulness and co-operation and possessing an approachable nature and an amiable attitude. As a consequence of acknowledging and implementing all these factors, one will render an important contribution in reinforcing socialization. One of the important aspects that needs to be taken into account is, one needs to reinforce a constructive approach. Furthermore, one will have to form cordial and amiable terms and relationships with each other. This is essential in encouraging socialization within and outside the homes. Therefore, it is well-understood, encouraging socialization is essential in leading to up-gradation of personality traits. The main concepts that are taken into account in this research paper are, understanding the meaning and significance of encouraging socialization, measures to be put into operation in encouraging socialization and advantages of encouraging socialization.